Attachment in Middle Childhood: An Evolutionary–Developmental Perspective. Issue 148 (June 2015) - Del Giudice, Marco
Abstract: Middle childhood is a key transitional stage in the development of attachment processes and representations. Here I discuss the middle childhood transition from an evolutionary–developmental perspective and show how this approach offers fresh insight into the function and organization of attachment in this life stage. I begin by presenting an integrated biological model of middle childhood and discussing the neurobiological mechanisms that support the middle childhood transition. I examine the potential role of adrenal androgens, focusing on their activational effects in interaction with early exposure to sex hormones. I then discuss three insights arising from the integrated model and apply them to the development of attachment in middle childhood. I consider the changing functions of attachment in light of social competition, the emergence of sex differences in attachment, and the model's implications for the genetics of attachment in middle childhood. © 2015 Wiley Periodicals, Inc.